Effect of Carbonation on the Leachability of Solidified/Stabilized Lead-Contaminated Expansive Soil. (11th February 2021) - Zha, Fusheng; Liu, Congmin; Kang, Bo; Xu, Long; Yang, Chengbin; Chu, Chengfu; Yu, Chuang; Zhang, Wei; Zhang, Jiwen; Liu, Zhenghong
Abstract : Lime, fly ash, and alkaline residue are used widely as effective binders to solidify/stabilize heavy metal-contaminated expansive soil. Carbonation, however, may influence the effectiveness of solidification/stabilization (S/S) by decomposing hydration products and decreasing pH, which would seriously damage the long-term durability of stabilized soils. This study focused on the variation of leaching characteristics of solidified/stabilized lead-contaminated expansive soils before and after accelerated carbonation under the leachant of pH 3 and 5 by the semidynamic leaching test. After semidynamic leaching, leaching indexes such as the effective diffusion coefficient ( D e ), leachability index ( Lx ), and slope ( r c ) were used to reveal the ion leaching mechanism. The results indicated that the amount of Pb 2+ and Ca 2+ leached out under different pH conditions increased after carbonation, which confirmed that carbonate on solidified/stabilized lead (Pb) had a negative impact. Additionally, the D e values of Pb 2+ and Ca 2+ varied in the range of 1.16 E − 10 cm 2 /s to 1.71 E − 07 cm 2 /s, which demonstrated that ion migration was low. The contaminated soil solidified by lime and AR could be used in "controlled utilization" as Lx was higher than 9, and the leaching process was controlled by a dissolution reaction according to the analysis of r c . Moreover, the strong acidic leachant (pH = 3) resulted in more ions leaching out and lower pH in leachate compared with a mildly acidic leachant. Finally, with literature and experimental results, we found that the main reason for the increase of lead ion filtration of the carbonation reduced the pH value of the matrix and made the hydration products denatured and decomposed.